2005
DOI: 10.1523/jneurosci.0454-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Na+/Ca2+ Exchangers and Mitochondria in Ca2+ Clearance at the Calyx of Held

Abstract: The clearance of Ca 2ϩ from nerve terminals is critical for determining the build-up of residual Ca 2ϩ after repetitive presynaptic activity. We found previously that K

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 39 publications
(59 reference statements)
10
131
1
Order By: Relevance
“…9 and 10). Previous studies have demonstrated that NCKX exchangers typically play a significant role in Ca 2ϩ homeostasis in environments where Ca 2ϩ flux is high and intracellular Ca 2ϩ levels rise substantially, in a temporally and/or spatially restricted manner (3,55). This suggests that NCKX4 may be localized in close proximity to the entry pathways that control Ca 2ϩ signaling downstream from the MC4R (see model in Fig.…”
Section: Volume 289 • Number 37 • September 12 2014mentioning
confidence: 98%
“…9 and 10). Previous studies have demonstrated that NCKX exchangers typically play a significant role in Ca 2ϩ homeostasis in environments where Ca 2ϩ flux is high and intracellular Ca 2ϩ levels rise substantially, in a temporally and/or spatially restricted manner (3,55). This suggests that NCKX4 may be localized in close proximity to the entry pathways that control Ca 2ϩ signaling downstream from the MC4R (see model in Fig.…”
Section: Volume 289 • Number 37 • September 12 2014mentioning
confidence: 98%
“…2؉ buffering during HFS at large and small MFBs Mitochondria have been suggested as a Ca 2ϩ sequestration mechanism at the axon terminals of many synapses (Tang and Zucker, 1997;David et al, 1998;David and Barrett, 2000;Billups and Forsythe, 2002;Suzuki et al, 2002;Kim et al, 2005;GarciaChacon et al, 2006 (Fig. 3Aa,Ab, black traces).…”
Section: Differential Contribution Of Mitochondria To Camentioning
confidence: 98%
“…The comparison is primarily focused on excitable cells, mostly neurons (for a more detailed role on mitochondria and Ca 2þ signaling, see Rimessi et al 2008 andSzabadkai andDuchen 2008). In the large glutamatergic presynaptic terminals of the calyx of Held, mitochondria contribute to increase the rate in [Ca 2þ ] i decay, when peak [Ca 2þ ] i is .2.5 mM (Kim et al 2005). This mitochondria-mediated increase in [Ca 2þ ] i decay closely resembles the action of the "slow buffer" PV in the same terminals (Muller et al 2007).…”
Section: Comparison Of the Physiological Effects Brought About By Cytmentioning
confidence: 99%